Rekonstruksi Etika Profesi Hukum terhadap Fenomena Moral Hazard Aparat Penegak Hukum di Era Disrupsi Keadilan Digital - Robert Sangkala; Ida Komala; Satria Ari Wibowo; Roif Roif; Ali Asari; Windi Setiawan; Firman Adi Candra (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
Legal professional ethics play an important role in maintaining integrity, justice, and public trust in law enforcement institutions. Ethical violations committed by legal professionals may weaken the credibility of the legal system and create injustice in society. This research aims to analyze the implementation of legal professional ethics in maintaining the integrity of law enforcement officials in Indonesia. The study uses a normative juridical method with statutory and conceptual approaches. The findings indicate that legal ethics are fundamental principles that guide judges, prosecutors, advocates, police officers, and other legal professionals in carrying out their duties responsibly. However, challenges such as corruption, abuse of authority, conflicts of interest, and weak supervision continue to affect ethical enforcement in legal practice. Strengthening ethical education, improving supervision systems, and enforcing professional codes of ethics are necessary to maintain the integrity of law enforcement institutions.